2021
DOI: 10.1007/s00401-021-02324-0
|View full text |Cite|
|
Sign up to set email alerts
|

α-Synuclein in blood exosomes immunoprecipitated using neuronal and oligodendroglial markers distinguishes Parkinson’s disease from multiple system atrophy

Abstract: The diagnosis of Parkinson’s disease (PD) and atypical parkinsonian syndromes is difficult due to the lack of reliable, easily accessible biomarkers. Multiple system atrophy (MSA) is a synucleinopathy whose symptoms often overlap with PD. Exosomes isolated from blood by immunoprecipitation using CNS markers provide a window into the brain’s biochemistry and may assist in distinguishing between PD and MSA. Thus, we asked whether α-synuclein (α-syn) in such exosomes could distinguish among healthy individuals, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
165
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(176 citation statements)
references
References 71 publications
(97 reference statements)
5
165
1
Order By: Relevance
“…Furthermore, we reported a lower EV concentration and an increased EV size in human plasma samples from patients with Alzheimer's disease (AD) and related dementias [35]. In line with our results, a reduced exosome concentration in serum/plasma was observed in multiple system atrophy and Parkinson's disease patients, compared with controls [36]. Increased levels of total Tau, phosphorylated Thr181 Tau, and Aβ42 in neurally derived blood EVs were demonstrated to be an early marker for AD and cognitive decline progression, thus supporting the use of circulating EVs as a sort of "liquid biopsy" [37][38][39].…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, we reported a lower EV concentration and an increased EV size in human plasma samples from patients with Alzheimer's disease (AD) and related dementias [35]. In line with our results, a reduced exosome concentration in serum/plasma was observed in multiple system atrophy and Parkinson's disease patients, compared with controls [36]. Increased levels of total Tau, phosphorylated Thr181 Tau, and Aβ42 in neurally derived blood EVs were demonstrated to be an early marker for AD and cognitive decline progression, thus supporting the use of circulating EVs as a sort of "liquid biopsy" [37][38][39].…”
Section: Introductionsupporting
confidence: 88%
“…In this regard, α-syn oligomers have been detected in the plasma of PD patients, but it remains to be determined if their presence precedes neuronal loss ( 104 ). A recent study by Dutta and colleagues confirmed the presence of α-syn in the blood of patients by exosome immunoprecipitation using neuronal and oligodendroglial markers, observing significantly higher α-syn concentrations in MSA exosomes compared to PD and healthy controls ( 105 ). The use of skin biopsies containing autonomic nerve terminals has also been suggested as a potential alternative source to investigate the seeding capability of α-syn, with comparable sensitivity and specificity to CSF ( 106 ).…”
Section: Introductionmentioning
confidence: 89%
“…More recently, in 2021, Dutta and colleagues analyzed the levels of α-Syn in neuronal (L1CAMimmunoprecipitated) and oligodendroglial (myelin oligodendrocyte glycoprotein-immunoprecipitated) EVs from serum or plasma of PD and MSA patients vs. HC [126]. They found that in both EV types, α-Syn levels significantly increased in the order HC<PD<MSA, in contrast with [125].…”
Section: α-Syn As Ev-transported Pd Biomarkermentioning
confidence: 99%
“…They found that in both EV types, α-Syn levels significantly increased in the order HC<PD<MSA, in contrast with [125]. Moreover, the ratio between α-Syn in oligodendroglial and neuronal EVs improved the distinction between the two synucleinopathies, with high sensitivity and specificity [126].…”
Section: α-Syn As Ev-transported Pd Biomarkermentioning
confidence: 99%